SUICIDAL BEHAVIOR ON PREVENTION OF ATVOR PSYCHOPROPHYPHYLACTIC MEASURES WITH ADOLESCENTS (Spectrum Journal of Innovation, Reforms and Development, 2022)
This article describes psycho-prophylactic measures to prevent suicidal behavior with adolescents and how to organize psycho-preventive work.